Analysis of the Moral Obligations of AI Developers Thru the Principle of Explainability in the Perspective of Kantian Deontological Ethics: A Qualitative Study - Rizma Fauziyah; Agung Winarno; Subagyo Subagyo (Eastasouth Institute, 2025)
The proliferation of